REVESTIMENTO A BASE DE NIÓBIO E TITÂNIO PARA PROTEÇÃO CONTRA CORROSÃO DO AÇO CARBONO SAE 1020 - Helleis, Rodrigo (2019)
Carbon steel is widely used by engineering due to its low cost and mechanical properties, however it resists poorly to corrosion, which makes it essential to use surface tratments even in mildly corrosive environments. The most commonly used surface treatments such as phosphating and galvanization presents great problems related to toxic wastes, therefore the study of new, less polutant forms of protection is important. Niobium and titanium are highly resistant to corrosion, this is due to the formation of a thin film of its oxides in the surface of the material when exposed to air. Synthetic coatings of these oxides have been studied mainly by the biomedical field to increase the corrosion protection behavior of implants and consequently increase its bicompatibility. Based on the abovementioned the objetive of the study was to develop and characterize a niobium and titanium oxides coating prepared by the Pechini method for the protection of carbon steel SAE 1020. For such, carbon steel (SAE 1020) plates were dip-coated in a resin prepared with ethylene glycol (EG), citric acid (CA), niobium ammonium oxalate as niobium precursor and titanium trichloride and potassium hexafluorotitanate as titanium precursors. The plates were immersed in the resin for 15 minutes and calcinated in a muffle oven for 1 hour. The eletrochemical characterization of the samples was performed by open circuit potential (OCP), eletrochemical impedance spectroscopy (EIS), potentiodynamic anodic polarization (PAP) and scanning vibrating electrode technique (SVET). The coatings were characterized morphologically and structurally by scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS) and X-ray diffraction (XRD). The electrochemical analyses indicated corrosion protection by the deposition of the oxides coating and determined that the best result was obtained for the resin prepare with K2TiF6 as titanium precursor and molar proportion EG:CA – 8:1, Nb:CA – 1:10 and Ti:CA – 0,6:10. The diffractograms presented a general amorphous characteristic for the oxides formed. Based on the SVET results and of the non-homogenous characteristic obtained for the morphology, it is concluded that the coating deposition protected the carbon steel against corrosion, however it is better applied as a pretreatment and not as a coating, such as phosphating, being necessary after the process, a layer of protective paint to grant the prtoection for a long time.